3D Ultralight Hollow NiCo Compound@MXene Composites for Tunable and High-Efficient Microwave Absorption - Wang, Hui-Ya; Sun, Xiao-Bo; Yang, Shu-Hao; Zhao, Pei-Yan; Zhang, Xiao-Juan; Wang, Guang-Sheng; Huang, Yi (Nano-micro letters, 2021)
Highlights Ultralight 3D NiCo compound@MXene nanocomposites that inherited hollow polyhedral skeleton and excellent conductive network were fabricated. Excellent electromagnetic absorption performance was achieved with optimal RLmin value of − 67.22 dB and ultra-wide EAB of 6.72 GHz under the low filler loading. Electromagnetic parameters and microwave absorption property can be distinctly or slightly regulated by adjusting the filler loading and decoration of Ti 3 C 2 T x nanoflakes. The 3D hollow hierarchical architectures tend to be designed for inhibiting stack of MXene flakes to obtain satisfactory lightweight, high-efficient and broadband absorbers. Herein, the hollow NiCo compound@MXene networks were prepared by etching the ZIF 67 template and subsequently anchoring the Ti 3 C 2 T x nanosheets through electrostatic self-assembly. The electromagnetic parameters and microwave absorption property can be distinctly or slightly regulated by adjusting the filler loading and decoration of Ti 3 C 2 T x nanoflakes. Based on the synergistic effects of multi-components and special well-constructed structure, NiCo layered double hydroxides@Ti 3 C 2 T x (LDHT-9) absorber remarkably achieves unexpected effective absorption bandwidth (EAB) of 6.72 GHz with a thickness of 2.10 mm, covering the entire Ku-band. After calcination, transition metal oxide@Ti 3 C 2 T x (TMOT-21) absorber near the percolation threshold possesses minimum reflection loss (RL min ) value of − 67.22 dB at 1.70 mm within a filler loading of only 5 wt%. This work enlightens a simple strategy for constructing MXene-based composites to achieve high-efficient microwave absorbents with lightweight and tunable EAB.